Exploratory Study of Cigarette Consumption Behavior: Perspective of Motive, Brand and Cigarette Advertisement - Wijaya, Tony; Nurhadi, Nurhadi; Kuncoro, Andreas Mahendro (Jurnal Economia, 2017)
Abstract: Exploratory Study of Cigarette Consumption Behavior: Perspective of Motive, Brand and Cigarette Advertisement. This study aims to explore the primary motives of cigarette consumption behavior, opinions related to the cigarette brand and advertisement as well as to identify the expense spent to consume cigarette. This study applied qualitative research. The sources of information were the students of Universitas Negeri Yogyakarta who were smokers. The technique of data analysis used in this study was qualitative descriptive. This study found that the reason underlined the respondents smoking, internally, were attempts, while the external factors that drove the respondent smoking were friends and relatives invitation, seeing the parents, joining the smoking environment or neighborhood, and looking cool according to the students. Brand was one of the considerations in choosing the cigarette related to the advertisement. Advertisement dominated by the cigarette producer brought more encouragement to the respondents than public service advertisements about the danger of smoking. The selling price of cigarette was also the main consideration by the respondent to smoke. The monthly expense spent for smoking was considerably high. Keywords: motive, cigarette consumptions, brand, advertisementAbstrak: Studi Eksplorasi Perilaku Konsumsi Rokok: Perspektif Motif, Merek, dan Iklan Rokok. Penelitian ini bertujuan mengeksplorasi motif dasar perilaku konsumsi rokok, pendapat terkait merek dan iklan rokok, serta mengidentifikasi biaya yang dikeluarkan untuk konsumsi rokok. Penelitian ini bersifat kualitatif. Informan yang menjadi sumber informasi dalam penelitian mahasiswa di UNY yang merokok. Teknik analisis data dalam penelitian menggunakan deskriptif kualitatif. Penelitian ini menemukan bahwa secara internal alasan yang mendasari responden merokok adalah coba-coba dan iseng sedangkan faktor eksternal yang mendorong responden merokok adalah diajak teman, kerabat atau melihat orangtua, ikutan karena lingkungan rokok dan terlihat lebih menarik atau istilahnya terlihat keren menurut versi mahasiswa. Merek menjadi salah satu pertimbangan pemilihan rokok yang terkait dengan iklan. Iklan yang didominasi dari produsen rokok membawa dorongan yang lebih kuat bagi responden untuk merokok dibandingkan iklan layanan masyarakat tentang bahaya rokok. Harga rokok menjadi pertimbangan utama bagi responden untuk mengkonsumsi rokok. Biaya yang dikeluarkan per bulan untuk konsumsi rokok responden tergolong cukup besar. Kata-kata kunci: Motif, Konsumsi Rokok, Merek, Iklan